2019
DOI: 10.1111/jace.16399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics investigation of the fracture mechanism of a glass‐ceramic containing cleavable crystals

Abstract: In this study on a novel glass‐ceramic containing hexagonal CaAl2Si2O8 crystals embedded in a SiO2–Al2O3–CaO glass, we used molecular dynamics simulations to unravel the toughening mechanism of the partially crystallized composite material. The crystalline phase is composed of alternate layers of SiO4/AlO4 tetrahedra and calcium ions. After careful modeling of crystals embedded in the glass matrix, we conducted crack propagation simulations using single‐notched models. We found that: (a) when a crack propagate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Because the modulus of metal is larger than that of glass matrix, the resultant SLG with lower modulus with larger deformation should be attributed to ductility due to metal particles which takes place when the load exceeds the yield strength. This toughening mechanism is distinguishable to the other hybrid glass system such as glass with phase-separation, and glass ceramics 28,29 because they increase fracture surface to impede total breakage. It is also largely different in scale from glass with nanoductility 30 induced by disconnecting bonds of network atoms either by introducing alkali ions or disconnecting bonds by electron beam irradiation.…”
Section: Discussionmentioning
confidence: 90%
“…Because the modulus of metal is larger than that of glass matrix, the resultant SLG with lower modulus with larger deformation should be attributed to ductility due to metal particles which takes place when the load exceeds the yield strength. This toughening mechanism is distinguishable to the other hybrid glass system such as glass with phase-separation, and glass ceramics 28,29 because they increase fracture surface to impede total breakage. It is also largely different in scale from glass with nanoductility 30 induced by disconnecting bonds of network atoms either by introducing alkali ions or disconnecting bonds by electron beam irradiation.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the microcracks induced by Vickers indentation were nondestructively observed for the first time (Figure 6). Our previous observation by SEM, as well as a theoretical approach using molecular dynamics simulation, indicated that the microcracks tend to travel in a glass-crystal interface [24,44]. Because the gap between two parallel microcracks and the size of the microcrack planes observed in Figure 6c agreed with the typical thickness and size of the hexagonal crystals, it is suggested that the microcracks in Figure 6c rendered the hexagonal crystal; hence, many microcracks were induced depending on the distribution of the hexagonal crystals around the imprint of the Vickers indentation.…”
Section: Discussionmentioning
confidence: 99%
“…PMMCS potentials make use of the Morse function for short-range interactions whose parameters were fitted to structural and elastic properties of various oxide and silicate crystals. The availability of parameters for many cation-oxygen pairs and its ability to predict the mechanical properties fairly accurately have made it a very popular choice for the study not only of multicomponent oxide glasses but also crystalline materials and oxide nanoparticles [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%